The Effect of Firm Characteristics on the Application of Advanced Management Accounting Techniques - Ghozali, Imam; Linnegar, Gary J (The International Journal of Accounting and Business Society, 1996)
This article evaluates management accounting practice of the Australian public listed companies and examines the relationship between certain contextual variables of ï¬rm characteristics and the application of advanced management accounting techniques. The survey research method is employed to gather evidence that contextual variables of size, age, type of industry and capital intensity have signiï¬cant inï¬‚uence on the application of advanced management accounting techniques Type I, ll and lll. Firm risk and leverage have signiï¬cant inï¬‚uence on the techniques Type ll and lll. But in term of ownership, there is no difference between domestic ï¬rms and foreign ï¬rms in applying management accounting techniques Type ll and lll.